Meningkatkan Kemampuan Menyunting Teks Karangan Dengan Metode Direct Instruction Kelas IX B SMP Negeri 16 Kupang - Udin Dile (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The study aimed to investigate the application of the direct instruction method in improving student ability to edit essay texts. Classroom Action Research was employed to get the data at Grade IX B, SMP Negeri 16 Kupang. The subject of this research was 30 students (15 male and 15 female). The research was carried out using two cycles which included the following steps: planning, action, observation, and reflection/analysis. Based on a study, the use of the Direct Learning Method can improve students' ability to find and correct spelling errors, word choice, sentence effectiveness, paragraph integration and discourse coherence. Based on observations in Cycle I and Cycle II, shows that the results obtained in Cycle I reached 40% learning completeness. Meanwhile, the results of Cycle II reached 80% of learning completeness.